ASP.NET MVC 4 and the Web API Building a REST Service from Start to Finish - Kurtz, Jamie; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
This one hundred page book focuses exclusively on how you can best use the ASP.NET MVC 4 Framework to build world-class REST services using the Web API. It sets aside much of what the ASP.NET MVC Framework can do, and focuses exclusively on how the Web API can help you build web services. You will not find any help on CSS, HTML, JavaScript, or jQuery. Nor will you find any help on the Razor view engine, HTML Helpers, or model binding. If you need this information then Pro ASP.NET MVC 4 is your perfect book. ASP.NET MVC 4 and the Web API: Building a REST Service from Start to Finish helps you build cutting-edge REST services using ASP.NET MVC 4 and the Web API in more depth and detail than any other resource. ASP.NET MVC has always been a good platform on which to implement REST, but with the advent of the Web API it has now become even better. This book will show you why it's great and how to get the most from it. Author Jamie Kurtz will take you from zero to full-blown REST service hero in no time at all. And you'll even learn how to incorporate some popular open source tools along the way: little or no experience with ASP.NET or the MVC Framework is required.
Keywords: Computer science; Computer Science; Computer Science, general